2016
DOI: 10.1080/0886022x.2016.1184940
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of anti-tuberculosis drug induced oxidative stress in kidneys bySpirulina fusiformisin a rat model

Abstract: Nephrotoxicity is a rare complication caused by anti-tuberculosis therapy-induced oxidative stress. The Cyanobacterium Spirulina fusiformis Voronikhin belonging to Oscillatoriaceae family is used traditionally as a source of antioxidants against oxidative stress. We aimed to investigate the efficacy of S. fusiformis in modifying isoniazid (INH) Histological examination of kidneys supported these findings. Results of the in silico analyses showed that selected active components of S. fusiformis interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
5
14
0
Order By: Relevance
“…Spirulina fusiformis (400 mg/kg b.w.) was administrated orally for 28 days (Chen et al 2005;Erejuwa et al 2011b;Martin and Sabina 2016).…”
Section: Dosagementioning
confidence: 99%
“…Spirulina fusiformis (400 mg/kg b.w.) was administrated orally for 28 days (Chen et al 2005;Erejuwa et al 2011b;Martin and Sabina 2016).…”
Section: Dosagementioning
confidence: 99%
“…It has been observed that Spirulina has a nephroprotective action against drug or toxicant that causes oxidative stress and renal damage. 9,15,16 Despite the benefits to renal health by Spirulina , there is not enough information about the effect of Spirulina on HgCl 2 -related glomerular and tubular renal dysfunction in AKI, although it has been reported that Spirulina and its components as phycobiliproteins and phycocyanin can reduce renal dysfunction in chronic kidney disease. 8 This work aimed to investigate whether phycobiliproteins and phycocyanin of Spirulina can improve HgCl 2 -related glomerular and tubular renal dysfunction as well as apoptosis process in kidney of rats.…”
Section: Introductionmentioning
confidence: 99%
“…Combination regimens of anti‐TB drugs could induce cytolysis and cholestasis 33. Although Sherry et al and Guo et al showed that this phenomenon might be related to FXR,18,34 the specific mechanism remained unclear. We suspected that UGT2B4 might involve, which led us to conduct this investigation.…”
Section: Discussionmentioning
confidence: 99%